Clinical and Evolutionary Features of SARS-CoV-2 Infection (COVID-19) in Children, a Romanian Perspective - Gheorghiță Jugulete; Daniela Pacurar; Mirela Luminița Pavelescu; Mihaela Safta; Elena Gheorghe; Bianca Borcoș; Carmen Pavelescu; Mihaela Oros; Mădălina Merișescu (MDPI AG, 2022)
Background: Given the potential for additional development to clarify a better knowledge of generally influence of COVID-19 upon the pediatric population, the clinical symptoms of SARS-CoV-2 infection in children and adolescents are still being explored. Morbidity in children is characterized by a variable clinical course. Our study's goal was to compare clinical aspects of 230 pediatric patients who analyzed positive for SARS-CoV-2 and were hospitalized between April 2020 and March 2022. Methods: This retrospective study aimed to compare the clinical characteristics of coronavirus disease 2019, (COVID-19) in two groups of pediatric patients hospitalized in the infectious disease clinical ward IX at the National Institute for Infectious Diseases "Prof. Dr. Matei Bals," Bucharest, Romania. Clinical characteristics of 88 patients (first group), admitted between April-December 2020 were compared with the second group of 142 children admitted between July 2021 and March 2022. Results: Of 230 children, the median age was 4.5 years, and 53.9% were male. Fever (82.17%) and sore throat (66%) were the most common initial symptoms. Rhinorrhea (42%), cough (34%) and diarrhea (41.74%), with abdominal pain (26%) were also reported in a considerable number of cases. 88 (36.21%) patients (first group) were admitted during the second wave in Romania, mostly aged <5 years old, and experienced digestive manifestations like fever (p = 0.001), and diarrhea (p = 0.004). The second group experienced different clinical signs when compared with the first group, with higher temperature and increased respiratory symptoms analogous to persons who suffer acute respiratory viral infections. The proportion in the second group increased by 23.48% from the first group, and the 0-4 age group for both groups had symptoms for a median interval of 5 days; age (0-4-years old) and length of stay were both proportionally inversely and required longer hospitalization (5 days), for the first group. During study time, the fully vaccinated children for 5-12 years old were 10%, and for 13-18 years old, 14.35% respective. We report two Pediatric Inflammatory Multisystem Syndrome (PIMS) in the second group, with favorable evolution under treatment. Comorbidities (obesity and oncological diseases) were reported in both groups and are risk factors for complications appearing (p < 0.001). All pediatric cases admitted to our clinic evolved favorably and no death was recorded. Conclusions: Clinical characteristics of pediatric patients with COVID-19 are age-related. In the first group, 85.29% of 0-4 years old children experienced digestive symptoms, whereas in the second group 83.78% underwent mild and moderate respiratory symptoms for the 5-12 age range. The potential effects of COVID-19 infection in children older than 5 years should encourage caregivers to vaccinate and improve the prognosis among pediatric patients at risk.